From elastomers to thermoplasts – Precise control of isotactic propylene structure and properties and the role of different structural elements in its mechanical behaviour. (20th December 2017) - Shcherbina, Maxim A.; Meshchankina, Marina Yu.; Odarchenko, Yaroslav I.; Machat, Martin; Rieger, Bernhard; Chvalun, Sergey N.
Abstract: Studies of polypropylene with different degrees of isotacticity have shown a way of the rational design of material with predetermined mechanical properties starting from the synthesis stage already – controlled introducement of stereodefects will allow the smooth adjustment of the Young's modulus and elasticity in the range from plastic to elastomer materials. It was also revealed that modern theoretical models of the elasticity can be successfully applied not only for the description of the mechanical behaviour of polymers, but also for better understanding of the mechanism of elasticity in them. While in the low crystalline materials deformation has Gaussian nature, in the materials of the intermediate crystallinity (30–40%) percolation takes place, and the cross-linking network becomes harder, manifesting the switch to the thermotropic behaviour of the material. Simultaneously the divide between cross- and slip-links becomes substantial, as an extensibility grows sharply. Graphical abstract: Highlights: Isotactic polypropylenes with different number of stereodefects were studied. Haward and Doi and Edwards models were successfully applied. Role of entanglements of different nature was elucidated. A way to precise control the mechanical properties of polymers was proposed.